Safety and immunogenicity of a SARS-CoV-2 mRNA vaccine (SYS6006) in minks, cats, blue foxes, and raccoon dogs - Huo, Hong; Wang, Jinming; Li, Chan; Xiao, Shuang; Wang, Han; Ge, Jinying; Zhong, Gongxun; Wen, Zhiyuan; Wang, Chong; Lang, Qiaoling; Chen, Lili; Wang, Zilong; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Minks, cats, and some other species of carnivores are susceptible of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and have a high risk of transmitting SARS-CoV-2 to humans. The development of animal vaccines can be an effective measure to protect animals against SARS-CoV-2 and reduce the potential risk of human infection. We previously developed a messenger ribonucleic acid (mRNA) vaccine SYS6006 that has been proven to be an efficient coronavirus disease 2019 (COVID-19) vaccine widely used in humans. Here, we further evaluated the safety and immunogenicity of SYS6006 as an animal COVID-19 vaccine candidate for SARS-CoV-2 susceptible animals or wild animals. SYS6006 was safe and immunogenic in mice and completely protected mice against mouse-adapted SARS-CoV-2 infection in the upper and lower respiratory tracts. SYS6006 was able to induce neutralizing antibodies against the SARS-CoV-2 wild-type, Delta, and Omicron BA.2 strain on day 7 after prime immunization, and two doses of immunization could enhance the neutralizing antibody responses and produce long-lasting potent antibodies for more than 8 months in minks and cats, blue foxes, and raccoon dogs, while all immunized animals had no abnormal clinical signs during immunization. These results provided here warrant further development of this safe and efficacious mRNA vaccine platform against animal COVID-19.